2014
DOI: 10.1109/jphotov.2013.2282747
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Post-Process Scribing for Reducing Cell to Module Efficiency Gap in Monolithic Thin-Film Photovoltaics

Abstract: The gap between cell and module efficiency is a major challenge for all photovoltaic (PV) technologies. For monolithic thin film PV modules, a significant fraction of this gap has been attributed to parasitic shunts, and other defects, distributed across the module. In this paper, we show that it is possible to contain or isolate these shunt defects, using the state of the art laser scribing processes, after the fabrication of the series connected module is finished. We discuss three possible alternatives, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…coupled module simulation framework to further investigate and reduce the cell-to-module efficiency gap [3], improve module reliability [6], as well as interpret thermal imaging measurements of solar modules [55].…”
Section: The Model Can Be Integrated Into An Electro-thermalmentioning
confidence: 99%
See 1 more Smart Citation
“…coupled module simulation framework to further investigate and reduce the cell-to-module efficiency gap [3], improve module reliability [6], as well as interpret thermal imaging measurements of solar modules [55].…”
Section: The Model Can Be Integrated Into An Electro-thermalmentioning
confidence: 99%
“…The performance gain has not been fully reflected at the module level (current highest module efficiency ~17% [2]). Therefore, there are opportunities for manufacturing and design improvements to reduce the cell-to-module efficiency gap [3]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that one of the main causes of non-uniformity of thin-film solar modules (e.g., CIGS and CdTe) is the lognormal distributed shunt [17], which contributes significantly to the cell-to-module efficiency gap [18]. The lognormal distribution of shunt can be inherent in thin-film technologies, which originated from the fact that grain size in poly-crystalline films is lognormal distributed regardless of the choice of materials.…”
Section: Potential Effect Of Increased Module Size On Energy Yieldmentioning
confidence: 99%
“…Changes in module design to reduce stress (e.g., the use of thicker glass) may be able to address some of these challenges if they were indeed observed in practice. Prior work suggests that although shunts or partial shading result in unsatisfactory degradation of module efficiency, novel geometry design and post-process scribing could be employed to enhance shadow tolerance for better reliability and isolate defects to improve overall module performance [18]. A complete understanding of the reliability of glass-glass modules in general is also still being developed.…”
Section: Potential Effect Of Increased Module Size On Energy Yieldmentioning
confidence: 99%
See 1 more Smart Citation